К филогении и классификации проктотрупоидных наездников (Hymenoptera, Proctotrupoidea) - Козлов, М.А. (Вестник зоологии, 1981)
Phylogenetic relations of Proctotrupoidea families are discussed on the basis of the extensive paleontological and recent material. A system of Proctotrupoidea is proposed based on their phylogeny.